A Virtual Approach to Promote Inter-Professional Learning (IPL) Between Biomedical Science and Medicine in Higher Education for the Benefit of Patient Care - Leadbeater, Wendy; Pallett, Ross; Dunn, Elizabeth; Bashir, Amreen (Frontiers in Public Health, 2021)
In the clinical setting, collaboration between multidisciplinary teams is core to providing effective patient care. The delivery of traditional interprofessional education is associated with a number of logistical challenges, which were heightened by the Covid-19 pandemic. This workshop was developed to bring together Biomedical Science and Medical students using an online platform. The workshop consisted of (1) defining interprofessional education, (2) introducing the role of the Pathology laboratory, (3) Professional registration with regulatory bodies and (4) an insight into Covid-19 laboratory diagnosis. The session was supported by mixed group breakout rooms and interactive polling. 34% of students completed a post-workshop online survey which included open and closed questions. Thematic analysis revealed a better understanding the role of the pathology laboratory in diagnosing disease, an increased awareness of the similarities and differences in the roles of a Biomedical Scientist and a Medic and the importance of a multi-disciplinary team in achieving effective patient care. Quantitative analysis of survey data revealed that the majority of students reported positive experiences of interprofessional education online. Approximately 90% of students agreed that the workshop enabled them to increase their understanding of their own roles within healthcare, in addition to increasing their understanding of the roles of other healthcare professionals. 74.3% of participants reported that working with students from a different programme provided an alternative perspective. 79% of students agreed that the online format enabled interactivity and discussion of the tasks. Of the 204 students, 85% engaged with the four polls during the workshop. This online workshop enabled discussion between degree programmes, enabled interactivity and allowed the learning outcomes to be met. Universities should embrace online platforms to provide a novel, engaging and effective interprofessional educational experience.